ROS, Notch, and Wnt Signaling Pathways: Crosstalk between Three Major Regulators of Cardiovascular Biology. (4th February 2014) - Caliceti, C.; Nigro, P.; Rizzo, P.; Ferrari, R.
Abstract : Reactive oxygen species (ROS), traditionally viewed as toxic by-products that cause damage to biomolecules, now are clearly recognized as key modulators in a variety of biological processes and pathological states. The development and regulation of the cardiovascular system require orchestrated activities; Notch and Wnt/ β -catenin signaling pathways are implicated in many aspects of them, including cardiomyocytes and smooth muscle cells survival, angiogenesis, progenitor cells recruitment and differentiation, arteriovenous specification, vascular cell migration, and cardiac remodelling. Several novel findings regarding the role of ROS in Notch and Wnt/ β -catenin modulation prompted us to review their emerging function in the cardiovascular system during embryogenesis and postnatally.